Hubungan antara Nilai Ankle Brachial Index dengan Kelembaban Kaki pada Pasien Diabetes Mellitus Tipe II: Relationship between Ankle Brachial Index Value and Foot Moisture in Type II Diabetes Mellitus Patients - Trisnadewi, Ni Wayan; Oktaviani, Ni Putu Wiwik Oktaviani; Adiputra, I Made Sudarma Adiputra (Bali Medika Jurnal, 2021)
Introduction: Diabetes mellitus (DM) is a degenerative and chronic disease, which requires long-term treatment and independent patient care, to prevent the effects of acute complications and long-term complications. Prolonged hyperglycemic conditions will cause chronic complications to the nervous system, namely diabetic neuropathy and decreased moisture in the feet. The purpose of this study was to determine the relationship between the ankle brachial index value and the humidity and sensitivity of the feet of type II DM patients. Method: This research method is non-experimental correlational study, with the research design used is cross sectional, with a total sample of 86 respondents taken by purposive sampling technique. Data collection used a mercury tensimeter, stethoscope and skin moisture analyzer. Results: The results of univariate analysis based on the Ankle Brachial Index value obtained a mean value of 0.99 (Minimum 0.83, Maximum 1.29) in the Normal ABI category, the moisture value of the feet obtained a mean value of 34.11 (Minimum 24.09, Maximum 47.65) in the less moisture category. The results of the analysis with the Spearman Range test obtained a p-value of 0.000 which indicates a relationship between the value of the Ankle Brachial Index and the moisture of the feet in type II DM patients. Discussion: The conclusion based on the results of this study it can be concluded that ABI is not the most dominant factor affecting the moisture of the foot skin in DM patients, so further research is needed to find the dominant factor.